Mapping Identity-Induced Marginalisation in India Inclusion and Access in the Land of Unequal Opportunities - Kale, Raosaheb K.; Acharya, Sanghmitra S. (Springer Nature Singapore : Imprint: Springer, 2022)
XXX, 491 p. 29 illus., 25 illus. in color.